Significant evidence for a schizophrenia susceptibility locus in the centromeric region of human chromosome - Shaw, S; Shields, G; Smith, AB; Larach, V; Wellman, N; Loftus, J; Nanthankumar, B; Razi, K; Stewart, J; Comazzi, M; Vita, A; Heffner, T; et al. (2001)
We have recently completed a genome-wide search for schizophrenia susceptibility genes in a collection of 301 pedigrees resulting in one significant (lod = 3.6, 10p14) and two suggestive (2cen, lod = 2.9; 3q27, lod = 2.3) linkage regions (DeLisi et al., submitted). As part of the schizophrenia genetics initiative, Faraone et al. (1998) reported linkage to markers in 2cen in a set of 43 pedigrees. In order to combine these results using the same genetic markers, analytic methods, and phenotypes, we have genotyped markers in a 40 cM region around the pericentromeric region of chromosome 2 in 42 NIMH pedigrees with at least 2 members diagnosed with schizophrenia from the schizophrenia. Both pedigree sets were combined together for a total of 343 pedigrees and the marker data were analyzed using both schizophrenia-only and schizophrenia plus schizoaffective disorder phenotypes. Multipoint non-parametric allele-sharing tests resulted in 2 peaks. Using a schizophrenia-only phenotype, a first peak occurred at D2S160 in 2q13 with a lod score of 5.4. A second peak occurred approximately 15 cM away at D2S139/D2S417 in 2p12 with a lod score of 4.0. The data were also analyzed using parametric methods and a schizophrenia-only phenotype using both dominant and recessive affecteds-only analyses. Tests under homogeneity resulted in a peak lod score of 3.8 at D2S160 using a dominant model (θ = 0.20). Under heterogeneity, the peak lod score increased to 4.0 at D2S160 (α = 0.40, θ = 0). In addition, several other markers in the 40 cM centromeric region of chromosome 2 had lod scores greater than 3. The data presented encompasses one of the largest pedigree collections for schizophrenia genetics studies and demonstrates highly significant results.